2010
DOI: 10.1029/2010jc006437
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the East China Sea Kuroshio and the Ryukyu Current as revealed by the self‐organizing map

Abstract: The self‐organizing map (SOM) is used to study the linkage between the two western boundary currents, the Kuroshio Current and the Ryukyu Current, through the Kerama Gap. Four coherent ocean current patterns, extracted from a numerical model output for the Kerama Gap area, are used to describe the variability of the Kuroshio current axis and the mesoscale eddies in the Ryukyu Current system. The temporal evolution of these four patterns shows a robust cycle with an average period of 120 days. The shift of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…When the maximum velocity of the Kuroshio current is located within the top 80 m of the water column, it ranges from 0.36 to 2.02 m s −1 ; when the maximum velocity is below 80 m, it ranges from 0.31 to 1.11 m s −1 [33]. Thus, the velocity of the Kuroshio current reduces from the southern Okinawa Trough to the middle Okinawa Trough (e.g., [58]), suggesting that the current variations of hydrothermal plume water in the Okinawa Trough are controlled by spatial variations in the intensity and position of the Kuroshio current (e.g., [33,58,59]). …”
Section: Variable Current Velocity In Hydrothermal Plume Watermentioning
confidence: 99%
“…When the maximum velocity of the Kuroshio current is located within the top 80 m of the water column, it ranges from 0.36 to 2.02 m s −1 ; when the maximum velocity is below 80 m, it ranges from 0.31 to 1.11 m s −1 [33]. Thus, the velocity of the Kuroshio current reduces from the southern Okinawa Trough to the middle Okinawa Trough (e.g., [58]), suggesting that the current variations of hydrothermal plume water in the Okinawa Trough are controlled by spatial variations in the intensity and position of the Kuroshio current (e.g., [33,58,59]). …”
Section: Variable Current Velocity In Hydrothermal Plume Watermentioning
confidence: 99%
“…6a-c. The SOM has been demonstrated to be more useful than conventional EOF to extract nonlinear information (Hsieh 2001(Hsieh , 2004Liu and Weisberg 2005;Reusch et al 2005;Liu et al 2006;Jin et al 2010), and the applications in oceanography and atmosphere can be found in previous studies (Hewitson and Crane 1994;Cavazos 2000;Hong et al 2004;Liu and Weisberg 2005;Iskandar et al 2008;Yin et al 2014, among others). All of these applications above suggest that the SOM is useful for oceanographic and meteorological feature extraction.…”
Section: Methodsmentioning
confidence: 84%
“…The self-organizing map (SOM) is an effective method for classification and feature extraction (Kohonen 1982(Kohonen , 2001Jin et al 2010). The method is very similar to k-means clustering (Bação et al 2005), and can be considered as a type of clustering technique (Jin et al 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the waters exchange among the Bohai Sea, Yellow Sea and the Sea of Japan, ocean current circulation may enhance genetic connectivity (Jin et al, 2010). The waters also exchange between the Yellow Sea warm current and the Kuroshio warm current (Li et al, 2000).…”
Section: Discussionmentioning
confidence: 99%